Y-STR Kits and Y-STR diversity in the South African population: A review - Sthabile Shabalala; Meenu Ghai; Moses Okpeku (Wolters Kluwer Medknow Publications, 2022)
The South African population consists of four ethnic groups, i.e., Blacks, Coloreds, Indians, and Whites, and is considered the most diverse conglomeration of humans. In addition to autosomal short tandem repeat (STR) variation, an important tool to study population diversity is Y-chromosome (Y)-STR analysis. Y-STRs aid in forensic investigations and provide essential data about paternal lineage origins. Y-STR kits consisting of an array of stable and rapidly mutating markers offer crucial information on a given population's genetic and haplotype diversity. This review discusses the development of Y-STR kits over the years and highlights some prominent Y-STR studies conducted on the South African population. The earliest Y-STR kit developed was the Y-PLEX™6, with the most recent being the UniQTyper™ Y-10 Multiplex. The South African population studies show varying data, with the "minimal haplotype" having low discrimination capacity among the ethnic groups and the UniQTyper™ Y-10 showing high genetic diversity among the ethnic groups of the country. There is a dearth of Y-STR studies on the South African population. With the advent of new Y-STR kits with increased discriminatory markers, additional studies are required to represent the South African population in the Y-STR databases. Considering the diversity of the South African population, establishment of a local/regional population database would be beneficial. In addition, data on the origins and prevalence of mutations and silent alleles should be obtained from STR datasets generated during kinship investigations (specifically, parentage tests) so that detailed information about the frequencies of mutations, silent alleles, and uniparental disomy in the South African population at Y STR loci can be estimated.